The Influence of Knowledge, Attitudes, and Self-Efficacy on the Preparedness of School-Age Children in Facing Earthquake Disasters - Janatri, Sri (STIKep PPNI Jawa Barat, 2023)
Aims: The study aimed to determine the effect of knowledge, attitude, and self-efficacy on preparedness and the simultaneous effect of knowledge, attitude, and self-efficacy on preparedness. Methods: This study uses a correlational research design with a cross-sectional approach. Population and research samples were taken by a total sampling of as many as 143 students in high school at Sukabumi-West Java and as many as 161 respondents. Data collection used a nonstandard questionnaire developed by researchers with answer choices using the Guttman scale. Results: Most of the mean and standard deviation values of knowledge 14.18 (2,906), attitude 42.69 (6,514), self-efficacy 35.77 (10,575), and preparedness 16.28 (4,076). There is a simultaneous effect of knowledge, attitude, and self-efficacy on preparedness (p-value <0.05). There is a simultaneous influence of knowledge, attitude, and self-efficacy on preparedness (value <0.05). Conclusion: There is an effect of knowledge, attitude, and self-efficacy on preparedness and a simultaneous effect of knowledge, attitude, and self-efficacy on preparedness. MTs Al-Mu'awwanah Kota Sukabumi needs to improve students' understanding of disaster preparedness through training and extracurricular activities focusing on knowledge, attitudes, and self-efficacy.